A critical content analysis of writing materials covered in Indonesian high school English textbooks - Renol Aprico Siregar; Didi Sukyadi; Fazri Nur Yusuf (Universitas Syiah Kuala, 2024)
Despite many studies addressing writing materials in English language learning textbooks in the Indonesian context, few reported the conformity of the English writing materials in senior high school textbooks intended for the 2013 curriculum to the genre of written language paradigm. The present study critically analyzed the existing writing materials covered in Indonesian senior high school textbooks. The data sources for this research were three English textbooks designed for three levels of senior high school students in Indonesia. The writing materials were selected from the textbooks as the representatives of the analysis objects. The data were analyzed following content analysis by integrating Brown (2004) as the conceptual framework. The results reveal that the writing materials are consistent with the framework. The books cover all text genres, including academic, professional, and personal writing. However, not all framework-informed sub-categories of texts are reflected in the writing materials of the examined textbooks. In addition, the evaluated textbooks emphasize student exposure to intensive writing tasks (grammatical transformation, short-answer sentence completion, and picture-cued tasks) and extensive writing tasks (paragraph construction, guided question and answer, and paraphrasing). These results highlight the need to align textbooks with the curriculum genre of the written language paradigm and to balance intensive and extensive writing tasks to prepare students for real-life writing situations.